2023
DOI: 10.1039/d3ra01581e
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-coated halloysite nanotube magnetic microspheres for carcinogenic colorectal hemorrhage and liver laceration in albino rats

Abstract: Sever blood lose in carcinogenic colorectal hemorrhage due to longitudinal ulcer, ultimately become fatal if left untreated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
0
0
Order By: Relevance
“…Likewise, the addition of HNTs enhanced the anti-inflammatory and analgesic effects of ketorolac and reduced gastric hemorrhagic ulcers and mucosal lesions in rats (Figure e) . Chitosan-coated HNT microspheres were found to alleviate carcinogenic colorectal hemorrhage in rats …”
Section: Biomedical Applicationsmentioning
confidence: 84%
See 1 more Smart Citation
“…Likewise, the addition of HNTs enhanced the anti-inflammatory and analgesic effects of ketorolac and reduced gastric hemorrhagic ulcers and mucosal lesions in rats (Figure e) . Chitosan-coated HNT microspheres were found to alleviate carcinogenic colorectal hemorrhage in rats …”
Section: Biomedical Applicationsmentioning
confidence: 84%
“…115 Chitosan-coated HNT microspheres were found to alleviate carcinogenic colorectal hemorrhage in rats. 116 A clinical study demonstrated that a traditional Chinese medicine called "Taohua Tang" prepared from halloysite, dried ginger, and rice, could alleviate diarrhea and promote mucosal recovery. This formulation is especially useful for improving clinical outcomes in patients with antibiotic-associated diarrhea.…”
Section: Gastrointestinal Disease Treatmentmentioning
confidence: 99%